The Cuban Economy - Ritter, Archibald R. M. (Book collections on Project MUSE., 2004)
Cuba faced an economic meltdown of catastrophic proportions in the early 1990s when covert subsidies from the former Soviet Union disappeared. This analysis addresses both the large questions of macroeconomic policy design and performance as well as key specialized topics.